CYBER STALKING ACTIVITY OF MILENIAL GENERATION IN URBAN SOCIETY IN INDONESIA - Sugiharto, Agus (International Review of Humanities Studies, 2020)
Millennial generation itself is often defined not by date of birth but also based on their behavioral and psychographic tendencies. This unique generation is a generation born in the internet age. Cyber stalking activities to ex-girlfriends or wives are often done, this is the reason why this cyber stalking activity exists and continues to grow, along with the many activities in social media, and the amount of social media used. It is a fairly large number, it seems that also experienced by the millennial generation, the activities carried out on the internet usual to obtain information. Methods in this study using qualitative method with sequential exploratory strategy. While theory used in the research is the theory of communication, theory of global village, theory negotiation advance, the theory of national resilience and social media theory. Cyber stalking has increased along with the easy access to the internet and mobile phone users owned smartphones. Cyber stalking activity is also done to co-workers, friends, boyfriend and ex-boyfriend. This means that cyber stalking activity will be a reasonable activity, self activity (private) even now is not uncommon to be public consumption. So that cyber stalking activity becomes something commonly done by millennial generation.